Functional impact of splice isoform diversity in individual cells - Yap, Karen (2017)
Alternative pre-mRNA splicing provides an effective means for expanding coding capacity of eukaryotic genomes. Recent studies suggest that co-expression of different splice isoforms may increase diversity of RNAs and proteins at a single-cell level. A pertinent question in the field is whether such co-expression is biologically meaningful or, rather, represents insufficiently stringent splicing regulation. Here we argue that isoform co-expression may produce functional outcomes that are difficult and sometimes impossible to achieve using other regulation strategies. Far from being a ‘splicing noise’, co-expression is often established through co-ordinated activity of specific cis-elements and trans-acting factors. Further work in this area may uncover new biological functions of alternative splicing (AS) and generate important insights into mechanisms allowing different cell types to attain their unique molecular identities.